Legal and Cultural Contexts of Parent-Teacher Interactions: School Councils in Canada - Brien, Ken; Stelmach, Bonnie L. (International Journal about Parents in Education, 2023)
Parents and teachers interact because of their shared responsibility for the welfare of the children in their care. Research indicates that teachers value parental involvement in their students’ education. There is also evidence that parents place a great deal of trust in their children’s teachers. This interaction, with significant influence on the learning outcomes of students, occurs within a complex set of legal frameworks and cultural contexts. These include such legal considerations as international treaties on family and children’s rights, national constitutional rights, and statutory rights and responsibilities of parents, teachers, and the state. Cultural factors include issues of engagement, marginalization, and power relationships. Societal evolution has also led to changing rights, responsibilities, and expectations for parents, teachers, and students. Parent-teacher relationships have also been affected by recent government initiatives to promote parental involvement in education through the creation of school councils. This paper, based on Canadian research on parental involvement in schooling and an analysis of Canadian and international legal principles, will illustrate the interplay of these legal and cultural considerations. The intent of this paper is to encourage better understanding of the complexity within the parent-teacher relationship.